The Sustainable Tourism Index: Policy And Regulatory Environment - Andy Mulyana; Ahmad Soleh; Ida Ayu Made Er Meytha Gayatri; Nihan Anindyaputra Lanisy (UNIVED Press, 2025)
The purpose of this study is to analyse the contribution of policy and regulatory environment in measuring the Sustainable Tourism Index of Tourism Villages in Indonesia. The research focuses on four tourist villages, namely Penglipuran (Bali), Nglanggeran (Yogyakarta), Setanggor (West Nusa Tenggara), and Belitar Seberang (Bengkulu). This research uses a mixed method approach. The Sustainable Tourism Index from The Economist Intelligence Unit was developed in measuring the Sustainable Tourism Index of Tourism Villages in Indonesia. The results showed that the contribution of the policy and regulatory environment category in the formation of the Sustainable Tourism Index in Indonesia was 35.77 or with an average indicator performance of 89.54%. All tourist villages in Indonesia have conducted cooperation between public and private stakeholders and have conducted an inventory of tourism assets. Most of the tourist villages have village regulations on local tourism, milestones and action plans, monitoring and evaluation metrics as well as leasing and licensing for tourism activities and have a stable political environment. However, not all tourist villages have implemented global standards. In order to increase international tourist arrivals, global standards are needed in the management of tourism villages in Indonesia.